Effect of solution pH on the dynamic of biosorption of Cr(VI) by living plants of Salvinia minima - Chocobar Ponce, Silvana (2015)
Salvinia minima is a widely distributed floating fern that bioaccumulates high concentrations of heavy metals and is a promising species for Cr(VI) removal from polluted waters. Metal bioaccumulation efficiency of aquatic plants can be affected by different factors such as surrounding pH and metal concentration. In this study we investigated the effect of solution pH on the biosorption and reduction of Cr(VI) in living plants of S. minima under both pH-stat (buffered) and pH-shift (unbuffered) conditions. Plants were exposed to 0, 5 and 20 mg L−1 Cr(VI) concentrations for 7 days under controlled conditions at pH 4.0, 6.0 and 7.6. Cr(VI) was determined using 1,5-diphenylcarbazide in presence and absence of KMnO4. Cr(III) concentration was estimated as the difference between Crtotal [Cr(VI) + Cr(III)] (with KMnO4) and Cr(VI) (without KMnO4) concentrations. Metal biosorption was significantly higher in acid buffered solution than in unbuffered solution, but the biosorption pattern was different indicating that solution pH could be a key factor controlling the removal of Cr(VI) by S. minima. The pH of acid unbuffered Cr(VI)-containing solutions was significantly increased during Salvinia growth. Contrarily no significant changes of pH were observed in unbuffered solutions without Cr(VI). Reduction of Cr(VI) to Cr(III) was significantly higher at lower pH. Visual symptoms of Cr(VI)-induced damage were less evident at lower pH. Results demonstrated that S. minima can survive and remove Cr(VI) at low pH values. This work indicates that selection of suitable aquatic macrophytes for potential application in heavy metal phytoremediation requires an additional focus regarding interactions among metal, solution pH, and plant performance.